Virological investigation and comparative genomic analysis of elephant endotheliotropic herpesvirus 1B infection in an Australian captive herd of Asian elephants (Elephas maximus) - Jack W. Wheelahan; Paola K. Vaz; Alistair R. Legione; Carol A. Hartley; Natalie L. Rourke; Michael Lynch; Bonnie McMeekin; Elizabeth C. Dobson; Joanne M. Devlin (PLoS ONE, 2026)
Elephant endotheliotropic herpesviruses (EEHV) pose a significant threat to the conservation of Asian elephants ( Elephas maximus ) worldwide, with a high mortality rate in young elephants. However, several components of EEHV virology remain underexplored, particularly for EEHV1B. This study describes a fatal case of EEHV1B infection in a nine-year-old Asian elephant from an ex situ conservation herd, examining herd viral dynamics, tissue viral loads and comparative genomics. This elephant succumbed to haemorrhagic disease within three days of developing clinical signs, despite therapeutic intervention. Quantitative PCR (qPCR) was performed on serial trunk washes and whole-blood surveillance samples collected before and after the clinical event, as well as on post-mortem tissues preserved in different storage media (DNA/RNA Shield, RNALater, and viral transport medium). Metagenomic next-generation sequencing of infected tissues was performed to characterise the complete viral genome, analyse variation from other published EEHV genomes and assess for evidence of viral recombination between EEHV subspecies. The affected elephant demonstrated a marked viraemia at onset of clinical disease, with viral load peaking at 5.47 x 10 6 viral genome equivalents per mL of blood, one day after the onset of clinical signs. Samples stored in viral transport medium yielded the greatest viral and host DNA recovery by qPCR, although tissues stored at −80 °C without media were still suitable for molecular detection. Whole genome sequencing demonstrated 96.0% pairwise nucleotide identity between the assembled genome (EEHV1B_AUP_01_2023, GenBank accession: PX651398) and the previously reported EEHV1B sequence (KC462164), and a maximum of 90.9% identity to published EEHV1A genomes, with evidence of recombination between the viral subspecies at several genomic regions. Viral recombination between EEHV subspecies may have significant implications for the pathogenesis of EEHV disease, the reliability of molecular diagnostics and the efficacy of vaccinations and anti-viral therapy.